How Children’s Participation in Sports Influences their School Engagement Levels - Yang Jiang; Bo Feng (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The provision of education to left-behind and migrant children play a crucial role in the advancement and progress of society. China is confronted with a significant number of left-behind children who experience a deficiency in fundamental education. This longitudinal study investigates the influence of sports involvement on the level of school engagement among left-behind and migrant children in China. The data was gathered from five provinces located throughout China. A sample size of 683 data points was selected through random sampling, encompassing diverse fundamental information pertaining to students, families, and school-related data. The data that was gathered underwent a standardisation process and reverse-scoring using the statistical software SPSS 26.0. The results of the study indicate that there is a notable disparity in the level of school engagement among left-behind (M = 4.34) and migrant children (M = 5.65) when compared to urban children (M = 6.02). Furthermore, the findings demonstrate a statistically significant and positive correlation between involvement in sports activities and the level of engagement in academic pursuits among the aforementioned group of children. The analysis further illustrates that there is a partial mediating effect of interpersonal skills in this relationship. This research highlights the beneficial effects of engaging in sports activities on academic involvement and emphasises the significance of interpersonal abilities. At the societal level, it is imperative for educational institutions, communities, and local administrations to enhance diverse mass sports organisations and effectively incorporate various public sports resources into the fabric of society. Establishing a sports participation network that integrates the home, school, and community at the national policy level is a commendable undertaking.